Encyclopedia of Environmental Microbiology 2003
DOI: 10.1002/0471263397.env288
|View full text |Cite
|
Sign up to set email alerts
|

Cold Adapted Microorganisms: Use in Biotechnology

Abstract: Underlying Principles and Molecular Genetic Technologies Cold‐Active Enzymes Bioremediation Some Future Applications of Cold‐Adapted Microorganisms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 197 publications
0
2
0
Order By: Relevance
“…These enzymes have the ability to support transcription and translation at low temperatures (Goodchild et al, 2004). Psychrophilic enzymes isolated from psychrophilic yeasts exhibit high activity at low and moderate temperatures and thus offer potential economic benefits (Allen et al, 2001). Kourkoutas et al, (2002) reported that psychrophilic yeast can be used in low temperature fermentation.…”
Section: Biotechnological Application Of Cold-active Enzymesmentioning
confidence: 99%
“…These enzymes have the ability to support transcription and translation at low temperatures (Goodchild et al, 2004). Psychrophilic enzymes isolated from psychrophilic yeasts exhibit high activity at low and moderate temperatures and thus offer potential economic benefits (Allen et al, 2001). Kourkoutas et al, (2002) reported that psychrophilic yeast can be used in low temperature fermentation.…”
Section: Biotechnological Application Of Cold-active Enzymesmentioning
confidence: 99%
“…As with biological potential, the high activity of psychrophilic enzymes offers economic benefits (Allen et al, 2001;Cavicchioli et al, 2002;Gerday et al, 2000;Margesin et al, 2003b;Margesin & Schinner, 1999;Russell, 1998). The goal of energy saving in large-scale processes in industrial fields and waste treatment, for instance, protease enzymes have been used for leather treatment and are carried out by cold-active enzymes instead of tap water at 37.…”
Section: Introductionmentioning
confidence: 99%